2019
DOI: 10.1186/s13640-019-0478-8
|View full text |Cite
|
Sign up to set email alerts
|

An online graph-based anomalous change detection strategy for unsupervised video surveillance

Abstract: Due to various accidents and crime threats to an unspecified number of people, many surveillance technologies have been studied as an interest in individual security continues to increase throughout society. In particular, intelligent video surveillance technology is one of the most active research areas in the field of surveillance; this popularity has been spurred by recent advances in computer vision/image processing and machine learning. The main goal is to automatically detect, recognize, and analyze obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…Although DBSCAN is a spatial data clustering technique, we have proven in prior research [ 35 ] that an adaptive graph clustering technique based on DBSCAN shows high performance in clustering real-world data. In addition, we confirmed that the spatial data clustering technique could be analyzed in the coordinate system of two-dimensional (2D) images in a previous study [ 36 ]. Based on the results of these preliminary studies, the proposed DTAA combines the coordinates of the bounding box with the feature vectors of the detected objects and extracts them as embedding vectors for clustering.…”
Section: Introductionsupporting
confidence: 86%
“…Although DBSCAN is a spatial data clustering technique, we have proven in prior research [ 35 ] that an adaptive graph clustering technique based on DBSCAN shows high performance in clustering real-world data. In addition, we confirmed that the spatial data clustering technique could be analyzed in the coordinate system of two-dimensional (2D) images in a previous study [ 36 ]. Based on the results of these preliminary studies, the proposed DTAA combines the coordinates of the bounding box with the feature vectors of the detected objects and extracts them as embedding vectors for clustering.…”
Section: Introductionsupporting
confidence: 86%
“…The study [17] proposed new approach for regression based on delegating classifiers to predict radon concentration in soil gas concentration and anomalies by delegating the samples to the next lower level that do not meet the desired threshold. The authors [18] employed SOM for data clustering in the first phase and then applied the shortest path algorithm to recognize anomalous events. A method based on statistical measure percentiles is used in supervised learning over the patterns of normal behavior to detect abnormal long periods of inactivity in a home [19].…”
Section: Related Workmentioning
confidence: 99%